Managerial attitudes and the leadership styles of university librarians in the Philippines - Cichon, Melchor F. (1986)
The objectives of this study are two-fold: 1) to describe the demographic characteristics of university librarians; and 2) to identify the managerial attitudes and leadership styles of the university librarians.